Redefining Womanhood: The New Woman and The Doll/Man-Woman Dichotomy in Late Victorian Literature - Howard, Brittany Leigh (My University, 2011)
This thesis deals with the New Woman's struggle to find a place within a society that could not entertain the concept of independent femininity. To Victorians, to be female was to be dependent, and therefore the idea of a woman who chose self-sufficiency over marriage was baffling. Period authors struggled to reconcile this enigmatic figure in their works, but developing endings proved difficult. Many writers married off their heroines to men who required them to compromise traits that made the women problematic traits such as independence or a desire to know oneself beyond one's role as wife or mother. Heroines who refused to suppress these aspects were rejected from society, existing as pitiful, isolated figures. A study of New Women heroines in three works George Egerton's "The Regeneration of Two," Grant Allen's "The Type-Writer Girl", and Bram Stoker's "Dracula"reveals that the primary concern for many women was losing one's own identity through marriage. When we consider Victorian femininity, we often think of the Angel in the House/Fallen Woman trope, which divides women into two categories: the virtuous wife and the corrupted whore; there is no place for women existing outside of this bifurcation. Yet these are not the actual but merely the perceived struggle at the heart of womanhood. Rather, the true choice for women was either marriage and sublimation of self, or self-actualization through financial independence. Because of this dichotomous understanding of femininity, women could choose only one role, either wife and mother, or "odd woman." Victorian society could not imagine the role of "working wife" or "working mother" because such roles blurred sex distinctions to an unfathomable degree. The New Woman brought to light the true crisis affecting women for centuries, namely that to be a part of acceptable society, a woman must sacrifice the most important part of herself—not her virtue, but her individuality. As she became an increasingly acceptable pop culture image, the figure of the New Woman functioned as a gateway to an acceptable alternative role for women.
Keywords: Howard; Victorian; feminism; literature; Egerton; Grant Allen; Bram Stoker